PENGARUH TINGKAT SUKU BUNGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PENGAMBILAN KREDIT PEMILIKAN RUMAH NASABAH DI PT. BANK TABUNGAN NEGARA KANTOR CABANG SOLO - Dian Wulan Sari; Kasidin Kasidin (STIE Atma Bhakti, 2020)
The research purposes were 1) determined the effect of the interest rate on the decision to take homeownership loans at PT. Bank Tabungan Negara Solo Branch Office; and 2) determined the effect of service quality on the decision to take the homeownership loans at PT. Bank Tabungan Negara Solo Branch Office. The research population is customers of PT. Bank BTN Solo Branch Office that takes non-subsidized BTN homeownership loans. Samples were 70 respondents. The questionnaire used in the study used a Likert scale with intervals of 1 to 5. The test equipment was used a reliability test used Cronbach's Alpha and a validity test was used Product Moment Pearson correlation. Data analysis was used multiple linear regression to determine the effect of interest rates and service quality on the decision making to take homeownership loans at BTN Solo. The results showed that the variable interest rate had a significant positive result, while service quality had a negative result on the purchase decision to take homeownership loans at PT. Bank BTN Solo Branch Office.